1993
DOI: 10.1111/j.1469-8137.1993.tb03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of O3 and SO2 on reproductive development in oilseed rape (Brassica napus L.). I. Pollen germination and pollen tube growth

Abstract: SUMMARY A single exposure of pollen of Brassica napus L. cvs Tapidor or Libravo to 100 nl l−1 ozone (O3) either in vitro or in vivo on the anthers of intact plants had no significant effect on either pollen germination or pollen tube growth. Exposure of dry pollen to 200 nl l−1 sulphur dioxide (SO2) also produced no significant effect. However, pollen germination was significantly reduced and pollen tube growth impaired in both cultivars when pollen was exposed in unbuffered incubation medium to 200 nl l−1 SO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…By contrast, pollen from tomato (Lycopersicon esculentum) and petunia (Petuniai hybrida) (Krause et al, 1975), lily (Lilium longiflorum ; Masaru et al, 1976) and oilseed rape (B. napus cv. Libravo ; Bosac et al, 1993) has been reported to be insensitive even to relatively high concentrations of ozone under some exposure conditions. Sensitivity to ozone has been shown to vary not only between but also within species.…”
Section: Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, pollen from tomato (Lycopersicon esculentum) and petunia (Petuniai hybrida) (Krause et al, 1975), lily (Lilium longiflorum ; Masaru et al, 1976) and oilseed rape (B. napus cv. Libravo ; Bosac et al, 1993) has been reported to be insensitive even to relatively high concentrations of ozone under some exposure conditions. Sensitivity to ozone has been shown to vary not only between but also within species.…”
Section: Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
“…§Indicates that only the inflorescences were exposed to ozone ; the vegetative and reproductive organs were both exposed in all other studies. Bosac et al, 1993Bosac et al, , 1994Bosac et al, , 1998, Wisconsin Fast Plants (Brassica campestris ; Stewart et al, 1996 ;Stewart, 1998) and P. major (Stewart, 1998) provide evidence that exposure to realistic ozone episodes at critical developmental stages can influence the reproductive structures directly, promoting significant effects on floral development, seed yield and quality, and seedling vigour. These studies also demonstrated substantial genotypic variation in sensitivity, and the existence of extensive compensatory flexibility which enables reproductive sites lost by abortion or abscission to be replaced, thereby contributing to the maintenance of seed yield.…”
Section:      mentioning
confidence: 99%
See 3 more Smart Citations